POLITICAL DETERMINANTS OF BUDGET DEFICITS: A SURVEY OF LITERATURE - Farah, Alfa (Universitas Negeri Semarang, 2010)
This paper provides a review of recent developments in the theory and evidence of political determinants of budget deficits. Specifically, we discuss five areas, namely; political system, government fragmentation, ideology, budget procedure and political budget cycles. We Â also provide evidence of recent studies.